ChemInform Abstract: Hetero‐Annulation Reaction Between 2‐Acylnaphthoquinones and 2‐Aminobenzothiazoles. A New Synthetic Route to Antiproliferative Benzo[g]benzothiazolo[2, 3‐b]quinazoline‐7, 12‐quinones. Issue 49 (December 2015) - Valderrama, Jaime A.; Rios, David; Muccioli, Giulio G.; Buc Calderon, Pedro; Brito, Ivan; Benites, Julio
Abstract: 2‐Acylnaphtoquinones generated from substrates (I) react with 2‐aminobenzothiazoles to form the title compounds (III).